Impacts of Corporate Structural Changes on Performance of Banks and Non-Bank Financial Institutions in Nigeria, 2005-2019 - Olaoye, Festus Oladipupo; Fakiyesi, Oyindamola Adesola; Jabar, Adebola Abass (ABUAD Journal of Social and Management Sciences, 2024)
This study investigated the impacts of corporate structural changes on performance of banks and non-bank financial institutions in Nigeria covering a period of 15 years (2005-2019). The capital structural change was captured with absolute change in debt equity ratio, total debt ratio, long-term debt ratio short-term debt ratio while the performance was measured with dividend per share and gross earnings. The study adopted ex-post facto research design which provides empirical solutions to research problems by using already existing data. The secondary data was extracted from the published financial report of the sampled firms. Population of the study included all the 14 quoted Deposit Money Banks (DMBs) and 25 Insurance Companies in operation in Nigeria. The sample size of the study is delimited to 10 quoted DMBs and 10 Insurance firms in Nigeria and this was achieved through random sampling technique. The collected data were analyzed using quantitative econometric techniques such as descriptive analysis, correlation analysis and panel regression analysis. It was discovered that when the model was controlled with firm size and asset tangibility, absolute changes in total debt ratio, absolute changes in long term debt ratio and absolute changes in short term debt ratio have a positive but insignificant effect on gross earnings of deposit money banks and insurance companies in Nigeria. Also, it was disclosed that there is a significant effect of absolute changes in the components of capital structure on dividend per share.